A 70-year study of femicides at the Forensic Medicine department, University of Bologna (Italy). (April 2022) - Giorgetti, Arianna; Fais, Paolo; Giovannini, Elena; Palazzo, Chiara; Filipuzzi, Ilenia; Pelletti, Guido; Pelotti, Susi
Highlights: Femicides represent a worldwide health issue and a hidden and constant phenomenon. Data on femicides should include different sources and research is limited. In recent decades, the victim of femicide is older compared to the past. Homicides committed by family members are increasing. The characterization of the phenomenon could help counteract violence against women. Abstract: Femicide is defined as the gender-related killings of women and girls or as an any intentional murder of women and it represents a worldwide health issue. Although it has gained a growing attention across the public and the media, true data on its prevalence and a characterization of the phenomenon are still scarce. The aim of the present study was to evaluate the characteristics of female homicides and femicides, which are necessary to design and monitor effective preventive efforts. Post-mortem examination reports of female homicides occurred in the judicial district of Bologna over a period of 70 years were revised. Characteristics of victims and perpetrators, circumstantial and post-mortem data were extracted. Overall, 172 female homicides were observed, including 103 femicides, with no significant changes over time. The mean age of victims increased over time and showed a statistically significant association with the victim-perpetrator relationship. Homicides committed by non-intimate partner family members increased. Our study unveiled that, in the past decades, femicide was a hidden but constant social phenomenon, despite the social, cultural and juridical changes. The research in forensic pathology could help bring to light trends, characteristics and risk factors to be considered for strategies to counteract violence against women.